Wykorzystanie rzeczywistych pluwiogramów do modelowania odpływu wód opadowych = Using raingauge-based rainfalls in modelling of runoff flows - Nowogoński, Ireneusz; Golik, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Results of raingauge-based rainfalls data analysis for period 1985-1986 in Zielona Góra were presented. Rainfall with the biggest intensity were chosen to obtain runoff flows at the outlet. Results were compared with data obtained using classic methods.
Keywords: kanalizacja deszczowa; modele symulacyjne; drainage network; simulation models